Molecular xenomonitoring for the assessment of lymphatic filariasis transmission in Jaffna and Trincomalee districts in Sri Lanka - Azizur Rahman, Mohammad (International Journal Of Community Medicine And Public Health, 2024)
Background: Lymphatic filariasis also known as elephantiasis is a neglected tropical disease causes by filarial parasites are transmitted to humans through infected female mosquito bite. The disease was formerly endemic in Sri Lanka and has been declared eliminated as a public health problem in 2016. However, LF transmission was not studied in detail in Jaffna and Trincomalee districts due to the long political unrest. The present study, LF transmission in mosquito was assessed by Molecular Xenomonitoring. Methods: A prior investigation was carried out to detect anti-filarial IgG4 in urine with ELISA and circulating filarial antigen in capillary blood with Filariasis strip tests. Subjects become positive in both testes were included their house location for mosquito collection to conduct MX. Surrounding residents were selected as target for mosquito collection with CDC gravid trap. Collected mosquitoes were dried and sorted in 827 pools (≤20 mosquitoes/pool). DNA was extracted and purified from all the pools and examined by Polymerase Chain Reaction to detect filarial DNA. Results: Total, 16,631 female C. quinquefasciatus mosquitoes were collected by CDC gravid traps and tested with PCR. All pools from Jaffna and Trincomalee districts were negative for W. bancrofti infection. But, four pools (0.67%) from Trincomalee district were positive for B. malayi infection which indicated possible resurgence of brugian filariasis. Conclusions: The result suggested no evidence of infection of bancroftian filarisis. However, identification of B. malayi filarial DNA in post elimination phase is concerning and warrant further investigation.